Computed Tomography Features and Clinical Prognostic Characteristics of Hepatoid Adenocarcinoma of the Stomach - Huang, Wen-peng; Li, Li-ming; Li, Jing; Yuan, Jun-hui; Hou, Ping; Liu, Chen-chen; Ma, Yi-hui; Liu, Xiao-nan; Han, Yi-jing; Liang, Pan; Gao, Jian-bo (Frontiers in Oncology, 2021)
Purpose: The purpose of this study was to describe the clinical, computed tomography (CT), and prognostic features of HAS to increase the awareness of this entity and determine its distinguishing features from non-HAS tumors. Methods: The CT features and clinical data of 47 patients with pathologically documented HAS were retrospectively analyzed, and the relevant differences between pure HAS (pHAS) and mixed HAS (mHAS) were determined. In addition, 141 patients with non-HAS tumors with the same T stage in the same period were selected as the control group. The data were compared between the two groups, and factors affecting the prognosis of HAS were analyzed. Results: The patients in the HAS group were predominantly men (n = 33), and the tumor location was mostly the cardia or fundus (n = 27). Differences in sex; serum AFP, carbohydrate antigen (CA)-125, and CA-724 levels; longest tumor diameter; degree of differentiation; vascular invasion; N stage, M stage, and tumor-node-metastasis (TNM) stage; thickest tumor diameter; plain CT attenuation; arterial-phase CT attenuation; CT attenuation difference between the venous and arterial phases; enhancement mode; and degree of enhancement were observed between the HAS and non-HAS groups. Among patients in the HAS group, 72.34% had pHAS and 27.66% had mHAS. The thickest diameter of the tumor and the longest and shortest diameter of the metastatic lymph nodes were greater in the mHAS group than in the pHAS group. The median progression-free survival and median overall survival times were shorter in the HAS group than in the non-HAS group. The factors affecting the prognosis of HAS were M stage, overall TNM stage, presence of vascular cancer emboli, and pHAS type. Multifactorial analysis revealed that M stage and pHAS type were independent risk factors affecting the prognosis of HAS. Conclusion: Patients with HAS often have advanced-stage disease at presentation and a worse prognosis than patients with non-HAS tumors. CT findings, combined with laboratory results, can support the diagnosis of HAS. However, the final diagnosis needs to be confirmed with histopathologic examination. If the postoperative pathologic findings reveal the mHAS type, rapid clinical intervention and detailed follow-up with CT are essential.